Cluster Preface: Heterogeneous Catalysis - Hierso, Jean-Cyrille; Uozumi, Yasuhiro (Synlett, 2016)
Jean-Cyrille Hierso is full professor of Chemistry since 2009, heading the group of ‘Organometallic Chemistry and Catalysis’ at the Institute of Molecular Chemistry at the University of Bourgogne Franche-Comté (UBFC). He has interest in the fields of organometallic chemistry, ligand design, homo- and heterogeneous catalysis, chemical physics, and material sciences. In 2011 he was awarded the National Prize for Coordination Chemistry from the French Chemical Society (SCF), and at the end of 2012 he was elected a junior Member of the French Professors Academy ‘Institut Universitaire de France’ (IUF).Yasuhiro Uozumi is a full professor at the Institute for Molecular Science (IMS) in Okazaki, Japan since 2000, and has also been appointed as a research team leader at RIKEN in Wako, Japan. He is interested in the fields of organic synthesis, organometallic chemistry, transition metal catalysis, and green chemistry. He was awarded The Chemical Society of Japan (CSJ) Award for Creative Work (2007), the Ministerial Award for Green Sustainable Chemistry (2007), the Inoue Prize (2010), and The Ministerial Commendation for Science and Technology (2014).
Keywords: sustainable chemistry; nanocatalysts; organocatalysts; gold; palladium; nanoparticles; peptides; polymer supports; inorganic supports; nanotubes; epoxidation; esterification; cross-coupling; C–H functionalization; oxidation; (hetero)arenes; Kinetics; supramolecular assembly; recovery; recycling